Sasaknese Traditional Games as a Medium for Strengthening Science Literacy: Preservice Teachers’ Perceptions - Wazni, M. Khairul; Kusuma, Dadang Warta Chandra Wira (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to explore the perceptions of preservice teachers regarding sasaknese traditional games as a medium for strengthening science literacy. This exploratory research was conducted at the Mandalika University of Education with a subject pool of 234 preservice teacher students. The research utilized a validated closed questionnaire instrument with responses gathered using a Likert scale. The data from this study were analyzed using quantitative descriptive statistics. The results of this study are Sasaknese traditional games have great potential as an effective medium for strengthening science literacy among preservice teachers. Positive perceptions were shown by the majority of respondents across various categories, including gender, semester level, and regional origin. Male students tended to show higher levels of agreement compared to female students, while students in their final semester (semester VII) demonstrated a deeper understanding and appreciation for the use of traditional games in science education. Similarly, positive perceptions were evenly distributed across the Lombok Island region, indicating that local wisdom is widely accepted as a contextual approach in education.